Post-Soviet media law & policy newsletter : Benjamin N. Cardozo School of Law - New York University. Center for War, Peace, and the News Media.; Benjamin N. Cardozo School of Law. Howard Squadron Program in Law, Media and Society. (New York, N.Y., United States :, 1993)
Current frequency: 12/year.Continued by: Communications law in transition newsletter.